2011
DOI: 10.1002/jms.1955
|View full text |Cite
|
Sign up to set email alerts
|

Disulfide bond cleavage in TEMPO‐free radical initiated peptide sequencing mass spectrometry

Abstract: The gas-phase free radical initiated peptide sequencing (FRIPS) fragmentation behavior of o-TEMPO-Bz-conjugated peptides with an intra- and intermolecular disulfide bond was investigated using MS(n) tandem mass spectrometry experiments. Investigated peptides included four peptides with an intramolecular cyclic disulfide bond, Bactenecin (RLCRIVVIRVCR), TGF-α (CHSGYVGVRC), MCH (DFDMLRCMLGRVFRPCWQY) and Adrenomedullin (16-31) (CRFGTCTVQKLAHQIY), and two peptides with an intermolecular disulfide bond. Collisional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(76 citation statements)
references
References 74 publications
3
71
2
Order By: Relevance
“…[23][24][25] In brief, the peptides of interest was dissolved in a 0.1 M NaHCO 3 buffer solution and then subjected to conjugation with o-TEMPO-Bz-NHS in DMSO by mixing. The o-TEMPO-Bz-conjugated peptides were purified prior to tandem mass spectrometry application, using the reversedphase solid phase extraction (SPE, Ultra-micro spin column C-18, Harvard Bioscience, Holliston, MA, USA) protocol.…”
Section: Methodsmentioning
confidence: 99%
“…[23][24][25] In brief, the peptides of interest was dissolved in a 0.1 M NaHCO 3 buffer solution and then subjected to conjugation with o-TEMPO-Bz-NHS in DMSO by mixing. The o-TEMPO-Bz-conjugated peptides were purified prior to tandem mass spectrometry application, using the reversedphase solid phase extraction (SPE, Ultra-micro spin column C-18, Harvard Bioscience, Holliston, MA, USA) protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Collisional activation of such radical ions results in side-chain and backbone cleavage with extensive sequence coverage. Lee et al introduced 2-[(2,2,6,6-tetramethylpiperidin-1-oxyl)methyl]benzoic acid (TEMPO-Bz, Scheme 1) as a free radical precursor bound to peptides through the N-terminus or at the ε-amine of lysine residues, [27][28][29] and is the tagging group employed in the present study. Collisional activation of the precursor peptide ions initiates homolytic cleavage of the labile NO-C bond, promoted by the remarkable stability of the released nitroxyl radical.…”
Section: Introductionmentioning
confidence: 99%
“…43,44 Another innovative approach is the development of the so-called free radical initiated peptide sequencing mass spectrometry (FRIPS-MS). [45][46][47][48][49] In FRIPS, a radical precursor is incorporated as a † This paper is to commemorate Professor Myung Soo Kim's honourable retirement.…”
Section: -42mentioning
confidence: 99%
“…Furthermore, the TEMPO-based FRIPS approach was shown to lead to the rupture of the disulfide (S-S) or the adjacent C-S bond in an exclusive manner, prior to peptide backbone dissociations. 48 Very recently, it was found that in negative ion mode, the radical-driven peptide backbone dissociations can be achieved in a single step, in contrast to the two-step peptide dissociations in positive ion mode. 49 The relative collision energy requirements for the two thermal activation steps in the TEMPO-based FRIPS were found to be responsible for the different peptide sequencing behaviors in the positive-and negative-ion modes.…”
Section: -49mentioning
confidence: 99%